Aroma precursors of Grignolino grapes (Vitis vinifera L.) and their modulation by vintage in a climate change scenario - Asproudi, Andriani; Bonello, Federica; Ragkousi, Vasiliki; Gianotti, Silvia; Petrozziello, Maurizio (Frontiers in Plant Science, 2023)
The influence exerted by different meteorological conditions during four consecutive years on aromatic potential of Grignolino grapes was investigated for the first time. The samples were collected from three vineyards characterized by different microclimatic conditions mainly related to the vineyard exposure and by a different age of the plants. Important differences as far as concern temperature and rainfall patterns during ripening were observed among the four years. Grape responses to abiotic stress, with particular emphasis on aromatic precursors, were evaluated using gas-chromatography coupled to mass spectrometry. The results highlighted significant differences among the vintages for each vineyard as to the berry weight and the aromatic precursors concentration. For the grapes of the younger-vine vineyard the content of aroma compounds showed a different variability among the vintages if compared to the old vine vineyards. Optimal conditions in terms of temperature and rainfall during the green phase followed by a warm and dry post veraison period until harvest favored all classes of compounds especially terpenoids manly in the grapes of the old vines. High temperature (>30°C) and low rainfall pattern before veraison led to high benzenoid contents and increased differences among vineyards as to berry weight, whereas the cooler aspect favored the terpenoid levels in the grapes of the South-East exposed vineyard. In hilly environment, conditions of lack of rainfall and high temperature that lately are characterizing the second part of berry development seem to favor the grape quality of Grignolino, a cultivar of medium-late ripening, by limiting the differences on bunch ripening, allowing a greater accumulation of secondary metabolites but maintaining at the same time an optimum balance sugar/acidity.